AI in humanitarian healthcare: a game changer for crisis response - Haykal, Diala; Goldust, Mohamad; Cartier, Hugues; Treacy, Patrick (Frontiers in Artificial Intelligence, 2025)
Artificial Intelligence (AI) is transforming humanitarian healthcare by providing innovative solutions to critical challenges in crisis response. This review explores peer-reviewed literature and case reports from 2001 to 2025, retrieved from PubMed, Scopus, and Google Scholar, using targeted keywords. Results indicate that AI enhances disaster prediction, disease surveillance, resource allocation, and mental health support through tools such as machine learning, natural language processing, robotics, and blockchain. Prominent applications include AI-powered early warning systems, chatbots for displaced populations, telemedicine platforms, and automated supply chain logistics. Ethical concerns such as data privacy, bias, and access inequities remain critical to responsible deployment. By uniting governments, NGOs, and technology providers, AI serves as a powerful tool to strengthen humanitarian healthcare systems, enhancing resilience and efficiency while ensuring better outcomes for vulnerable populations during crises.